Expansion of cytochrome P450 and cathepsin genes in the generalist herbivore brown marmorated stink bug - Raman Bansal; Andy Michel (BMC Genomics, 2018)
Abstract Background The brown marmorated stink bug (Halyomorpha halys) is an invasive pest in North America which causes severe economic losses on tree fruits, ornamentals, vegetables, and field crops. The H. halys is an extreme generalist and this feeding behaviour may have been a major contributor behind its establishment and successful adaptation in invasive habitats of North America. To develop an understanding into the mechanism of H. halys’ generalist herbivory, here we specifically focused on genes putatively facilitating its adaptation on diverse host plants. Results We generated over 142 million reads via sequencing eight RNA-Seq libraries, each representing an individual H. halys adult. The de novo assembly contained 79,855 high quality transcripts, totalling 39,600,178 bases. Following a comprehensive transcriptome analysis, H. halys had an expanded suite of cytochrome P450 and cathepsin-L genes compared to other insects. Detailed characterization of P450 genes from the CYP6 family, known for herbivore adaptation on host plants, strongly hinted towards H. halys-specific expansions involving gene duplications. In subsequent RT-PCR experiments, both P450 and cathepsin genes exhibited tissue-specific or distinct expression patterns which supported their principal roles of detoxification and/or digestion in a particular tissue. Conclusions Our analysis into P450 and cathepsin genes in H. halys offers new insights into potential mechanisms for understanding generalist herbivory and adaptation success in invasive habitats. Additionally, the large-scale transcriptomic resource developed here provides highly useful data for gene discovery; functional, population and comparative genomics as well as efforts to assemble and annotate the H. halys genome.